Management of Patient With Caustic Ingestion Injury: A Case Report - Supriadi; Budi Widodo; Brinna Anindita (Institute of Medico-legal Publications Pvt Ltd, 2021)
The ingestion of caustic substances, both accidental and voluntary, determines a complex syndrome,characterized by severe, often irreversible, visceral lesions, with still remarkable mortality in highlycompromised patients. Al36-year-old woman came to Emergency-Room with the chief complaints ofblackish vomiting about 4ltimes after drinking liquid to clean the bathroom floor. Patients with findings ofgrade 2B esophageal injury, pangastritis and gastric ulcer on endoscopy have high the risk of perforationand complications. Endoscopy done within 12lhours and no later than 24lhours following caustic ingestionto classify mucosal injury subsequent to caustic ingestion is useful to determine the severity of injury,particularly in suicidal cases, and thus helpful in predicting outcomes. Patient threat with rehydration withnormal saline, total parenteral nutrition, pump omeprazole, injection of methylprednisolone, antibiotic,and sucralfate. Consultation with the Psychiatry department has been conducted psychoeducation andpsychotherapy.